2021
DOI: 10.1002/ptr.7142
|View full text |Cite
|
Sign up to set email alerts
|

The p53/p21/p16 and PI3K/Akt signaling pathways are involved in the ameliorative effects of maltol on D‐galactose‐induced liver and kidney aging and injury

Abstract: Successive evidence has established that maltol, a flavor‐enhancing agent, could provide resistance to oxidative stress‐induced tissue injury in various animal models though its benefits for aging‐induced liver and kidney injuries are still undetermined. In the present work, for demonstrating maltol's ameliorative effect and probable mechanism against aging‐induced liver and kidney injuries, D‐galactose (D‐Gal)‐induced animal in vivo and HEK293 cells in vitro models were established and results demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Food & Function animals. 31 In our present study, D-gal injection for 8 weeks blocked the Nrf2/HO-1/NQO-1 antioxidant defense pathway in mouse kidneys and livers. LYC supplementation increased the expression of Nrf2, HO-1 and NQO-1 and decreased the level of β-galactosidase.…”
Section: Papersupporting
confidence: 55%
See 2 more Smart Citations
“…Food & Function animals. 31 In our present study, D-gal injection for 8 weeks blocked the Nrf2/HO-1/NQO-1 antioxidant defense pathway in mouse kidneys and livers. LYC supplementation increased the expression of Nrf2, HO-1 and NQO-1 and decreased the level of β-galactosidase.…”
Section: Papersupporting
confidence: 55%
“…Aging-related chronic liver and kidney diseases are common clinical conditions in the elderly and might cause increased mortality. 31 Elevated oxidative stress may trigger cell damage, thereby leading to accelerated aging and chronic degenerative diseases. 31 d -Gal is a reducing sugar that occurs naturally in the body and in many foods, 5 and mounting evidence demonstrates that high levels of d -gal injection for 6–8 weeks could result in the generation of ROS and subsequently accelerate oxidative stress and inflammation and induce the degeneration of numerous organs, such as the kidneys, liver and brain, which is similar to the characteristics of naturally aged animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P21 is an inhibitor of cyclin-dependent kinase and multiple studies demonstrated a tumor suppressive role of P21 in tumorigene-sis [38,39]. The main mechanism of P21 to prevent cell cycle progression is to inhibit the expression of CCNE1 and PCNA, thereby reducing the expression of tumor growth factor and blocking the progress of cell cycle [40][41][42]. In addition to PCNA, we also focused on other two proteins, CCNE1 and P21, that are related to cell proliferation [36].…”
Section: Mechanisms Of Scs Inhibited Colorectal Cancer 291 Scs Inhibits the Growth Of Ht-29 By Regulating The Expression Of Genes Involvementioning
confidence: 99%
“…In our transcriptome dataset, a series of genes involved in apoptosis were found to be differentially regulated after SCS treatment. PI3K is an intracellular phosphatidylinositol kinase, which participates in the regulation of PI3K/Akt signaling pathway, facilitating cell proliferation, and promotes cell apoptosis [42]. Bad is known as a pro-apoptotic protein, which can trigger and promote cell apoptosis but is inactivated in cancer cells [22].…”
Section: Scs Inhibits the Growth Of Ht-29 By Promoting Apoptosis Of Tumor Cells In Vivomentioning
confidence: 99%